Optimizing posyandu balita with cross-sector support in Salakan Potorono Bantul hamlet building - Jannah, Putri Isriyatil; Trisasri, Ruri; Eliana, Desy; Yanuari, Nabela Putri; Awaludin, Awaludin (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: Posyandu Balita is one of the Indonesian government's strategic efforts to improve the health and welfare of toddlers through community-based health services. Posyandu Balita has provided services such as monitoring child growth and development, immunization, administering vitamin A, and health education for mothers and families. The involvement of all components of society in the implementation of Posyandu Balita Widuri is very much needed, such as policymakers, community leaders, health workers, health cadres, academics, and the community to create synergy in posyandu services that can be felt by the entire community. This research aims to find out and identify the optimality of Posyandu Balita for cross-sector support in Salakan Potorono Hamlet.Methods: The method used is qualitative by conducting interviews with resource persons consisting of Community Health Center Health Workers, Head of Salakan Hamlet, Health Cadres, and the Community who regularly carry out Posyandu Balita.Results: The results obtained from the interview were that the service at the Posyandu Balita was excellent because it was by the posyandu service flow determined by the Ministry of Health. Apart from that, support from health workers such as providing health education training and posyandu services to health cadres, carrying out monthly monitoring and evaluation of posyandu services, and advocating to local governments to create excellent posyandu services for toddlers. Support from the Hamlet Head has also been implemented optimally, such as the use of village funds for posyandu activities and the welfare of Health cadres. Health cadres involved in posyandu activities have maximally carried out their obligations. Health cadres always increase capacity in knowledge and implementation in posyandu services. So that the community can feel the benefits of the posyandu activities that are carried out every month.Conclusion: The conclusion in this research is that Posyandu Balita Widuri is located in Salakan Potorono Hamlet, Banguntapan, Bantul has been optimal in terms of health services because of the support from across sectors that have played a role so far.